KEMAMPUAN SISWA KELAS III SD INPRES OLALAIN KECAMATAN ROTE TENGAH DALAM MEMBACA NYARING MELALUI PENGGUNAAN APLIKASI LETS READ ASIA - Andriyani A.D Lehan; Paulina Riwu Ga; Cindy Marbela Atikha Tulle (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
The purpose of this study was to describe the ability of third grade students of SD Inpres Olalain in reading aloud using the lets read Asia application. The data collection techniques used were tests and observations. The subjects of this study were third grade students totaling 13 people, 8 males, and 5 females. The data analysis technique is descriptive qualitative. Based on the results of data analysis of research on the ability to read aloud using the lets read Asia application for third grade students of SD Inpres Olalain out of 13 students studied, 38.5% were in the very good category, 46.1% were in the good category, and 15.4% were in the sufficient category. Based on the presentation of the scores, it can be concluded that the average score obtained by the class is 75. This shows that the level of ability of third grade students of SD Inpres Olalain in reading aloud has reached the average KKM 65.